Analysis of SIHA 2.1 Application Acceptance for HIV/AIDS Data Recording and Reporting with the UTAUT Model - Kari Artati, Diah; Maya Rani, Destri; Rizqulloh, Lutfiyah (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2023)
Rapid progress in the field of Information and Communication Technology (ICT), including in the health sector. ICT is being rapidly integrated into health systems to address issues related to the accessibility and delivery of digital health services. Through a website-based HIV Information System (SIHA) for integrated recording and reporting of HIV/AIDS and STIs. The SIHA 2.1 application must be used simultaneously by health workers at Indonesian health service facilities. To measure health workers' interest in using the SIHA 2.1 application, researchers conducted research using the UTATUT method. This method is expected to explain the application of the SIHA 2.1 Application in the use of information technology. This study aims to analyze the acceptance of the SIHA 2.1 Application among health workers in Central Java Province. Using qualitative methods in this research and sampling techniques using total sampling with a total of 56 respondents. The research results show a significant relationship between social influence, facilitating conditions, and habits on health workers' interest in using the SIHA 2.1 application. It is hoped that the results of this research will continue to increase the use of the SIHA 2.1 application.